The Analysis of Land and Building Tax Mandatory Compliance in Increasing Regional Tax Revenues in Buleleng District: Analisis Kepatuhan Wajib Pajak Bumi dan Bangunan Dalam Meningkatkan Penerimaan Pajak Daerah di Kabupaten Buleleng - Putri, Shefira Marina Putri; Ni Luh Gede Erni Sulindawati (Universitas Pendidikan Ganesha, 2024)
To increase its regional tax revenue, Buleleng district government collects land and building tax (PBB) directly through the Buleleng Regency Regional Financial and Revenue Management Agency (BPKPD). PBB is one of the regional tax revenue sources that has potential. However, the expected targets had not been optimal. One of the reasons for this was the lack of awareness of taxpayers in paying their tax obligations. This research aimed to determine the level of mandatory compliance, inhibiting factors, and minimization efforts for the inhibiting factors. This research was descriptive and quantitative with compliance ratio analysis techniques. The data sources of this research came from primary and secondary data with data collection methods through observation, interviews, and documentation. The research findings indicate: (1) the compliance level of land and building taxpayers in Buleleng Regency was 68.80% in 2019 (compliant), 61.64% in 2020 (sufficiently compliant), 55.93% in 2021 (sufficiently compliant), and 47.33% in 2022 (non-compliant). (2) Inhibiting factors leading to a decrease in taxpayer compliance stem from both internal and external factors. (3) Efforts undertaken involve addressing internal deficiencies as a means to reduce external factors.